METODE SOLFEGGIO SEBAGAI UPAYA PENINGKATAN KEMAMPUAN BERNYANYI SISWA DI KELAS VII SMP NEGERI 1 LUHAK NAN DUO - Radot Fernando; Olan Yogha Pratama (Universitas Negeri Padang, 2026)
This study aimed to improve the singing ability of seventh-grade students at SMP Negeri 1 Luhak Nan Duo, particularly in intonation, through the implementation of the solfeggio method. The research employed Classroom Action Research (CAR) conducted in two cycles, including planning, implementation, observation, and reflection. The subjects were students of class VII.7 in the 2025/2026 academic year. Data was collected through observation, tests, and documentation, and analyzed qualitatively and quantitatively. The results indicated a significant improvement in students’ singing ability from the pre-cycle to Cycle II. The improvement was reflected in better intonation and pitch accuracy through systematic solfeggio exercises, including scales, arpeggios, vocal warm-ups, and melodic training using ear training and sight singing. Thus, the solfeggio method proved effective in enhancing students’ singing skills, learning motivation, and musical understanding.